Optimizing 21st Century Skills Based on Cognitive Style by Implementing Figma-CTLLM in Poaceae Diversity Learning - Yudhistian, Yudhistian; Cintamulya, Imas (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
So far, cognitive style-based critical thinking, collaborative, and communication skills have yet to be utilized optimally. Additionally, there has been no research on optimizing 21st-century skills in cognitive style through the implementation of Figma Contextual Teaching Learning Learning Media (Figma-CTLLM). The research aims to optimize critical thinking, communication, and collaboration skills based on reflective and impulsive cognitive styles by implementing Figma-CTLLM in Poaceae diversity learning. The type of research is quantitative descriptive research. The research subjects consisted of 26 students. Research instruments include MFFT sheets, critical thinking and communication skills in written form test sheets, and collaboration skills observation sheets, all of which had been validated and proven reliable for use. The data analysis technique was carried out descriptively and quantitatively in three stages. The research results showed that eight students had a reflective cognitive style, and eight had an impulsive one. The results of the analysis of each skill show that there is no significant difference in critical thinking, communication, and collaboration skill scores between students with a reflective and impulsive cognitive style. This is proven by the average percentage value for each skill in the same category, which is very high among students with a reflective cognitive style and impulsiveness. This was also confirmed by the Mann-Whitney U test for each skill with a significance value (p) above 0.05 (p>0.05). Based on the results, the implementation of figma-CTLLM can optimize critical thinking, communication, and collaboration skills in students with reflective and impulsive cognitive styles in Poaceae diversity learning.